Perancangan Sistem Informasi Warga Bintara Jaya berbasis Android dengan Waterfall Software Development Life Cycle - Putri Handayani; Aji Setiawan (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
Rukun Tetangga / Rukun Warga is an inseparable part of Indonesian citizens ranging from administrative needs to social service needs such as information for residents, selection of new RT and RW leaders. The high interest of citizens towards services involving the RT head and other administrators often collided with the activities and daily activities of the administrators, resulting in limited and obstructed services for residents. This study aims to find the concept of system models that are needed by citizens to create ease in the management of messages and communication between the right citizens so that the time constraints that occur can be reduced. The research begins with designing a problem-based analysis design with the waterfall method. The method consists of sequential processes beginning with the analysis phase, system design, coding, implementation and maintenance of the system. The stages of system analysis, business process modeling using the Unified Modeling Language approach are used by use case and activity diagrams. The results of the study concluded that the application of the waterfall method could have an impact on the system development process to be more systematic and measurable, the system built was in accordance with what was expected by the residents.